The Influence of Financial Literacy, Financial Inclusion, Fintech Payment Gateway, and Digital Marketing on Financial Performance of MSMEs in Central Java - Triska Juliyani; Andwiani Sinarasri; Alwiyah; Fatmasari Sukesti; Mohammad Ridwan (IECON: International Economics and Business Conference, 2025)
This research endeavors to ascertain the impact of financial literacy, financial inclusion, fintech payment gateways, and digital marketing on the financial performance of MSMEs in Central Java. Employing a quantitative research design, this study utilizes primary data. The population under investigation comprises 193,932 MSME actors within the Central Java region. A purposive sampling method was applied, resulting in a total of 100 respondents. Data collection instruments were designed using a likert scale, and the analytical procedures were performed utilizing WarpPLS version 7.0. The results disclose that financial literacy imparts a positive and statistically significant effect on financial performance. Conversely, financial inclusion fails to exhibit a significant association with financial performance. Moreover, the adoption of fintech payment gateways manifests a positive and significant influence, while digital marketing reveals a negative yet statistically insignificant effect on financial performance. Collectively, the concurrent impact of financial literacy, payment gateways, and digital marketing has been empirically validated to exert a favorable influence on financial performance, as indicated by an R-squared value of 69.7%